Volatiles in the Loki’s Castle and Jan Mayen vent fields of the ultra-slow spreading Knipovich and Mohns Ridges - Lilley, M. D.; Pedersen, R. B.; Thorseth, I. H.; Lupton, J. E.; Olson, E. J.; Früh-Green, G. L.; Baumberger, T. (Geochimica et Cosmochimica Acta, 2009)
ISSN:0016-7037 ISSN:1872-9533